Pembangkit Listrik Tenaga Surya Terapung sebagai Solusi Berkelanjutan di Wilayah Terbatas Lahan: Analisis Bibliometrik - Reza Abdulrahim Tanjung; Rafi Ahmad; Mhd Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the development of research on floating photovoltaic (FPV) power plants as a sustainable solution for land-limited areas using a bibliometric approach. The analysis shows that 1,423 documents were published during the observation period. The number of publications increased significantly from 2022 to peak in 2025. China was the country with the highest contribution to publications, with research topics dominated by solar energy, renewable energy, and solar power generation.Keyword analysis reveals that major research themes include solar energy, renewable energy, and solar power generation, while floating photovoltaic remains an evolving topic. In addition to addressing land scarcity issues, FPV technology offers additional benefits such as improved solar panel efficiency and reduced water evaporation. However, technical, economic, and environmental challenges remain important concerns for future studies. Overall, FPV demonstrates strong potential as an innovative renewable energy solution that supports sustainable energy development in areas with limited land availability.